The lost diary of M : a novel - Wolfe, Paul, 1947- (Harper, an imprint of HarperCollinsPublishers, 2020)
An engrossing debut novel that cannily reimagines the extraordinary life and mysterious death of bohemian Georgetown socialite Mary Pinchot Meyer, secret lover of JFK, ex-wife of a CIA chief, sexual adventurer, LSD explorer and early feminist living by her own rules. She was a longtime lover of JFK. She was the ex-wife of a CIA chief. She was the sister-in-law of the Washington Post<U+2019>s Ben Bradlee. She believed in mind expansion and took LSD with Timothy Leary. She was a painter, a socialite and a Bohemian in Georgetown during the Cold War. And she ended up dead in an unsolved murder a year after JFK<U+2019>s assassination. The diary she kept was never found. Until now. . . .